Agricultural protectionism and multilateral trade negotiations in the GATT - O'Connor, Helen (1994)
The 7 year long GATT Uruguay Round (UR) of trade negotiations saw the first concerted attempt to reform world trade in agricultural products which was badly distorted by government policies to support domestic fanners. From the outset agriculture was the single most divisive issue on the 15 point agenda, with conflicts between the USA and the EC severely hampering the reform process. This study provides a review, and analysis, of the alternative strategies proposed by the main participants in the UR, and the final UR settlement, agreed in December 1993; it also provides an examination of the policy options open to governments wishing to support farm incomes with minimal distortions to world markets. The main participants accepted relatively early in the Round that an Aggregate Measure of Support (AMS) would be needed to quantify the existing level of internal support and then monitor reductions in it. Differences of opinion as to the calculation of such an AMS existed until 1990 when the main participants proposed that the AMS be based on the DECO Producer Subsidy Equivalent (PSE), but adjusted for differing policy coverage and the method of measuring market price support. Therefore, the PSE and the changes to the PSE suggested by the major participants in the UR are examined, giving the un surprising conclusion that by 1990 the USA and Cairns Group (CG) of exporting countries were calling for a far greater reduction in agricultural support than the EC. In addition, the USA and CG required that there be separate reductions in border protection and export subsidisation while the Ee contended that an AMS should capture all agricultural policies so that separate commitments would not be required. A partial equilibrium, dynamic, stochastic simulation model, covering 7 main trading areas, for wheat is developed to examine this contention; using the EC's 1990 proposals for reform, it is found that a reduction in the AMS does lead to a commensurate fall in import tariffs, but not in export subsidisation. The final UR agreement is analysed, using the model developed previously to determine whether the commitments in each of the 3 areas (internal support, border protection and export subsidisation) are compatible, in the sense that the different targets can be met simultaneously. The conclusions of this analysis are that the EC and USA are likely to have considerable difficulty in meeting the commitment to reduce the quantity of subsidised exports if the current agricultural policies are continued. Finally, it is acknowledged that although a significant aim of the agreed UR programme is raising world prices above what they would otherwise have been, it also has the effect of limiting the policy options of governments wishing to provide income support to fanners. The analysis suggests that the need to meet the UR commitment on export subsidisation will force the USA to cut expenditure on the Export Enhancement Program, and the EC to reduce intervention prices further and increase the amount of effective set aside. In addition, the cost of the compensatory payments policy is likely to result in continued budgetary crises after 1996.